Designing pro-health competition policies in developing countries - Vitor Henrique Pinto Ido (South Centre, 2020)
Competition law and policy has become an important tool for countries to promote access to pharmaceuticals. How can countries design and enforce competition policies that are suitable to the particularities of developing countries? What are the main anti-competitive tactics in the pharmaceutical sector, and how should they be dealt with? This paper deals with these issues, taking into account the socio-economic relevance of access to health products. It finds that developing countries should apply their competition laws in the pharmaceutical sector more actively, and that there is ample policy space under international law to do so. It provides an overview of the way in which competition policies have been applied in some industrialized and developing countries and explores how such policies can be designed and implemented in the context of developing countries.
Keywords: 300; Access to Medicines; Competition Law; Competition Policy; Compulsory Licenses; European Commission; Flexibilities; Health; Industrial Policy; Innovation; Intellectual Property; International Competition Network (ICN); International Law; Organisation for Economic Co-operation and Development (OECD); Patent; Pharmaceuticals; Research and Development (R&D); South-South Cooperation; TRIPS; TRIPS Council; UNHLP on Access to Medicines; United Nations Conference on Trade and Development (UNCTAD); United Nations Development Programme (UNDP); Voluntary License; World Health Organization (WHO); World Intellectual Property Organization (WIPO); World Trade Organization (WTO)